La place de la langue française dans la société cambodgienne contemporaine : enjeux linguistiques, identitaires et politiques - Raphaël Grosbois-Josse (Lengas)
This article delves into the influence of the French language on Cambodian society, drawing on qualitative studies conducted in collaboration with the National Institute of Education of Cambodia. By employing models such as the Ecology of Pressures and the Language Management Theory, it aims to comprehend the impact of the French language on the contemporary Cambodian identity, public perceptions of this foreign language, the life trajectories of Cambodian students, and current language policies. The study illuminates the unique significance and role of the French language in the postcolonial context of Cambodia and its ramifications for education and Cambodian society as a whole.